German call centers in Istanbul: Beyond the global and the local - Neitzert, Alina Belinda. (Thesis (M.A.)-Bogazici University. Institute of Social Sciences, 2008., 2008)
The 1990s witnessed the rise of call centers as a new form of work organization. The 2000s saw the next stage of the call center phenomenon in the form of large-scale outsourcing of call center operations to low-wage countries. A little-known case of call center offshoring is the existence of German call centers serving the German market from Turkey, especially from Istanbul. This case of offshoring is distinguished from other instances by the fact that these call centers do not rely on a native population that speaks the other country's language for historical reasons, but rather recruit their staff from among Turks who grew up in Germany and later "returned" to Turkey to work, thus reversing established patterns of work migration. The phenomenon of the German call center industry in Istanbul is examined here by method of participant observation carried out in one call center in Istanbul. The research has two foci of attention, on the one hand the call centers themselves, their origins, development and work processes, and on the other hand the people working there and the motivations that characterized their "return" to Turkey. The results of the study show that the rapid growth experienced by the German call center industry in Istanbul in its early years has come to an end by now, that the sector has consolidated itself and looks set to remain a part of Istanbul‟s economic landscape. With regard to the motivations for employees "decisions to "return" to Istanbul, it was found that in the majority of cases the location of close family members in Turkey was a major determining factor, while economic concerns played a minor role.
Keywords: Call centers.